PENGEMBANGAN PRODUK BUBUR UBI JALAR UNGU (Ipomea batatas) SEBAGAI ALTERNATIF PRODUK PANGAN DARURAT - Hermawan Seftiono; Intan Asmaradika (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2020)
Emergency food is food that designed and produced for directly consumed, and supplying humans daily nutritional needs in emergency conditions. Purple sweet potato porridge is an alternative for emergency food product that can directly consumed and also as effort for food diversification because it use purple sweet potato as carbohydrate source. Emergency food must easy to distribute, so one of the method is by using retort pouch as the packaging. The aims of this study is to analyze changes of critical parameters (colour, pH, and microbiological contamination) during storage period and to determine the shelf life of purple sweet potato porridge products. This study shows that the most preferred formulation of purple sweet potato porridge is Formulation F2 with 250 grams of purple sweet potato, 150 grams of sweetened condensed milk, and 500 ml of water. Shelf life of purple sweet potato porridge product based from colour changes parameter is 30 days, however based from microbiological contamination parameters the product didn’t meet national standard of Indonesia (SNI) requirements after two weeks of storage.